A Phenomenological Study on the Quality of Life Among Patients with Osteoarthritis Admitted for Rehabilitative Physiotherapy in a Private Hospital in Kuala Lumpur - R. (III) P. DIOSO; R. TANGGAYA (ASEAN Journal on Science and Technology for Development, 2015)
The aim of this study is to explore patients’ experiences and how their rehabilitation and physiotherapy at a private hospital in Kuala Lumpur, Malaysia has affected their quality of life (QOL) due to osteoarthritis (OA).  In addition, this study also aims to explore patients’ perspectives of the rehabilitation and physiotherapy for their OA before and after which affects moreover their QOL. The seven domains of the QOL were the physiological, social, financial,environmental, psychological, level of independence and spiritual – aimed to guide the theme of the interview sessions. A qualitative design was used. Of the 50 patients purposively enrolled only six were selected using inclusion and exclusion criteria.  Thematic analysis addressed the seven domains of the QOL for data analysis.  A 60-minutes interview session was audio-recorded.  The rehabilitation therapy was explored on all seven domains of the QOL. Of the six respondents four explored their lived experiences on the social and environmental domain, while fiveon the physiologic domain. The spiritual, psychological, level of independence and financialdomains were mostly explored by the six respondents that have affected their QOL.